Notice: Commencing the retaining pile and jet grouting pile in Zone C - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the notice of commencing retaining pile and jet grouting pile in Zone C of BRACU new campus project.